FACTORS INFLUENCING BREEDING FARMERS’ DECISIONS ON SELLING MARKETABLE RICE SEEDS IN BENGKULU PROVINCE - Triana, Ari; Yuliarso, M. Zulkarnain; Putra Utama, Satia (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
Bengkulu Province has the potential to meet the need for rice seeds. However, not all of these potential seeds are sold by captive farmers as rice seeds. Farmers' decision making in selling their seed production is influenced by internal and external factors. The aim of this research is to: 1) analyze farmers' decisions in selling prospective rice seeds; 2) analyze the factors that influence farmers' decisions in selling prospective rice seeds. This research was conducted by interviewing 104 rice seed farmers in six sub-districts in North Bengkulu Regency and South Bengkulu Regency. The decision to sell prospective rice seeds to farmer farmers was analyzed descriptively. What factors influence the decision to sell prospective rice seeds to breeder farmers are analyzed using Multinomial Logistic Regression. The research results show that there are three decisions to sell prospective rice seeds to breeder farmers, namely: 1) consumption rice (9.6%); 2) prospective seeds and rice for consumption (73.1%); 3) seed candidates (17.3%). Factors that have a significant influence on the decision to sell prospective rice seeds to farmer farmers in Bengkulu Province are farming experience, number of people in the family and family income as well as the length of time farmers have to get money from selling prospective seeds.